Contribution of IT in Scientific Research: A Case of Economic Sciences - Mora, Tania (2025)
IT are very important support tools for administrative management, for education and for research; every day it is more and more noticeable how they contribute to different scientific fields. The objective of this work is to demonstrate the contribution of IT to research in the area of economic sciences.  Using the incremental development method combined with Scrum, a web application was created using HTML, CSS and JavaScript technologies.  The structure is modular and the Integrated Development Environment (IDE) allows adapting various development environments.  The main result is that the application facilitates data management in a more efficient way; in addition, it allows self-management, cost savings (time and personnel) and minimizing errors. It also makes it easier to take research across borders, as the system is available to any Spanish-speaking company.  Thus, IT is a tool that allows the development of new sources of information and the generation of new research areas.